If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3-9d+6=9-4d
We move all terms to the left:
3-9d+6-(9-4d)=0
We add all the numbers together, and all the variables
-9d-(-4d+9)+3+6=0
We add all the numbers together, and all the variables
-9d-(-4d+9)+9=0
We get rid of parentheses
-9d+4d-9+9=0
We add all the numbers together, and all the variables
-5d=0
d=0/-5
d=0
| 50k+100=40+130 | | -6(10-4f)=-3(-12-8f | | 7(x+9)=9*5 | | 3(3a+5)=60 | | y-120=130 | | -4-3x=1-4x | | 2/3z-11=13 | | 7r+12=-23 | | 1a-1a=999 | | 8(x+4)-4=x-1 | | 3x+32=6x+14 | | -2+-4=-3+9x | | 7r+12=23 | | Y+10=-4y | | 7r-12=-23 | | 2/3p+3p=3/5 | | 5x+32=6x+3 | | 16x+20=20x+15-4x+5 | | A(t)=-t(2)+6t | | 6x-36=219 | | 2(3x+4)=2x-1+x | | F(n)=3+5/3n | | 12–7y=–4.8 | | 15.–1/5w–4=–2 | | 6+8n=9n+3 | | 9.6÷=1.6y | | 9+8x=-24-5x | | 6v+11=17 | | 2x-2=x+1x= | | 8-5m=-6m | | 3x+2=2x=23 | | 3x^2-8=39 |